Consumption of Vitamin K and Vitamin A Are Associated With Reduced Risk of Developing Emphysema: NHANES 2007–2016 - Shen, Tianjiao; Bimali, Milan; Faramawi, Mohammed; Orloff, Mohammed S. (Frontiers in Nutrition, 2020)
Chronic obstructive pulmonary disease (COPD) comprising of emphysema and chronic bronchitis are the most common chronic respiratory diseases that impart a huge economic and clinical burden. Factors other than smoking and air pollutants can cause inflammation and emphysematous changes in the lung airspaces or alveoli have been understudied. Using a cross-sectional study design, we assessed the association of dark green vegetables, vitamin K and Vitamin A with emphysema status among adults at U.S. These nutrients have a role in lung biology. A complete case NHANES data (n=17681) was used. After adjusting for modifiable and non-modifiable confounders, consumption of recommended amounts of vitamin K was associated with 39% decrease in odds (Odds Ratio: 0.61; 95% CI: 0.40-0.92, P-val: 0.02) of emphysema. Similarly consumption of recommended amounts vitamin A dose was associated with 33% decrease in odds (Odds Ratio: 0.67; 95% CI: 0.44-1.00, P-val: 0.05) of emphysema. Vitamin K shows an inverse association suggesting that it may be important in slowing the emphysematous process. Vitamin A is important in maintaining the anti-inflammatory process. Together vitamin K and vitamin A are important in the lung health